1155 CORONARY ARTERY DISEASE AND SEVERE AORTIC STENOSIS IN THE COVID-19 ERA: A CASE REPORT. (15th December 2022) - Spinali, Martina; Sorrentino, Sabatino; Sportelli, Martina; Bruno, Federica; Panarello, Alessandra; Aquila, Iolanda; Polimeni, Alberto; Mongiardo, Annalisa; Indolfi, Ciro
Abstract: An 81-years-old with a history of hypertension, dyslipidemia, and chronic ischemic heart disease with prior stent implantation of right coronary artery in 2011. Due to its poor compliance, no recurrent symptoms, and, finally, the COVID-19 pandemic, the patient did not perform any cardiological follow-up during these years. Unfortunately, the last six months he has reported the onset of dyspnea and typical angina due to moderate efforts, undervalued by the patient. Because of the rapid worsening of dyspnea and typical angina in the last 5 days, he went to the local emergency department (ED). The role in/role out routine exams performed in the ED documented a COVID-19 infection. At the ED, his vital signs were normal, with a blood pressure of 135/75 mm Hg, heart rate of 74 regular beats/min, body temperature of 36.5 °C, oxygen saturation of 97% in ambient air, and respiratory rate of 16/min. Of note, the chest x-ray was normal, as well as no alterations were documented at the CT scan performed a few hours later. First-line blood sample tests were within range except for Hb 10 mg/dl. Therefore, a cardiological evaluation was requested. Electrocardiogram (ECG) showed inverted T-waves in V1-4 leads, and echocardiography showed normal left ventricular ejection fraction (FE 55% Simpson), left ventricular anterolateral wall hypokinesia, and severe aortic stenosis (V max 4.78 m/s, Gr max 4.78 m/s, Gr medium 59 mmHg). Since myocardial necrosis enzymes were increased (T-hs 118.7 ng/dl; CK-MB 6.3 ng/L; NT-ProBNP 761 ng/dl), leading to the suspicion of acute coronary syndrome the patient underwent coronary angiography, showing critical stenoses of the left descending artery (LAD), circumflex (LCX), I obtuse marginal (IOM), and patent stent of the right coronary artery. Therefore, the Heart team deemed the patient at high operatory risk choosing, in agreement with the patient, for a percutaneous coronary intervention (PCI) followed by TAVR. Accordingly, the patients underwent PCI of LAD with the implantation of a Xience-Serra 3.0×15 mm and PCI of LCX with the implantation of an Onyx 2.75×18 mm stent. After COVID -19 resolution, which happen 7 days later, the patient was moved to our cardiology department. Two days later in the same procedure, we performed the first PCI of I-OM with the implantation of a Xience Sierra 3.0×18 mm stent following a TAVI with the implantation of Evolute Pro valve 29 mm. The post-procedure echocardiogram showed an optimal valve position with a transvalvular mean pressure gradient of 4 mm Hg. After six days post-TAVI, for a complete atrioventricular block, the patient also underwent a pacemaker implantation. The patient was finally discharged after 10 from TAVI. Discussion: This case report offers several foods for thought. First, the COVID-19 pandemic has negatively affected primary and secondary prevention, even for patients affected by cardiovascular disease. Our patient has postponed clinical checks even when the symptoms reappeared, also because of the concerns lead by the COVID-19 pandemic. Second, completeness and timing of coronary disease revascularization, which in this case was staged and performed before TAVI. Finally, the late occurrence of advanced heart block requiring PM implantation. For instance, in an era of fast-track TAVI, more studies are warranted to identify patients who are at higher risk of late PM implantation.